A behavioral genetic investigation of conceptualizations of resilience in a female twin sample. Issue 6 (27th February 2020) - Sawyers, Chelsea; Kurtz, Erin D.; Sheerin, Christina; Maes, Hermine H.; Kendler, Kenneth S.; Amstadter, Ananda B.
Abstract: Background: Great variability exists in response to stressful or traumatic events, leading to an interest in the construct of resilience as a trait and an outcome. The etiologic sources of variability across differing conceptualizations of resilience are poorly understood. Methods: Using behavioral genetic methods in a sample of 2, 056 female twins, the present study sought to (a) examine the etiologic sources of a trait‐based self‐report measure of perceived resilience (PR), (b) determine the genetic and environmental overlap with an outcome‐based measure of resilience, as defined by the absence of psychiatric symptoms after stressful life events, previously used by our research team (discrepancy‐based psychiatric resilience [DBPR]), and (c) determine the etiologic overlap of these two resilience measures with major depressive disorder (MDD). Results: PR was modestly (11%) heritable. A moderate degree of genetic overlap (39%) and a nominal amount of environmental overlap (3%) were found between the two alternative measures of resilience. Genetic factors that influence PR accounted for 3% of MDD heritability, whereas 31% of MDD heritability was due to DBPR genetic factors. Conclusions: Findings of a higher genetic correlation between the outcome‐based resilience measure and MDD compared to the trait‐based measure and MDD suggest gene‐finding efforts may benefit from considering the multifaceted nature of resilience and that resilience is best understood as both a phenotypically and genetically heterogeneous construct.